Nurses’ COVID-19 fears and patient safety attitudes in the pandemic - Efil, Sevda; Turen, Sevda; Demir, Elif (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The fear experienced by nurses during the COVID-19 pandemic may threaten patient safety. This study was conducted with the aim of examining nurses’ COVID-19 fears and attitudes to patient safety in the pandemic. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The research had a descriptive and cross-sectional design. The research sample consisted of 245 nurses working at a teaching and research hospital in Istanbul, Turkey’s most populous province. Research data were collected in June–July 2021. A Nurse Characteristics Form, the Fear of COVID-19 Scale (FCV-19S) and the Patient Safety Attitude Questionnaire were used to collect data. The data evaluation was performed using descriptive statistics, Student t test, one-way variance (ANOVA), and Pearson correlation analysis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The nurses’ mean score for fear of COVID-19 was 16.67±6.88, and their mean score for patient safety attitude was 141.70±27.78. Their COVID-19 fear levels and mean patient safety attitude scores were found to differ according to their intention to leave the job, their education on COVID-19 and their age. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Nurses’ experiencing of physical, social and psychological problems relating to the COVID-19 pandemic should be followed up in the long term.